Nature of Science as Portrayed in the Middle School Science and Technology Curriculum: The Case of Turkey - Kemal Izci (Journal of Education in Science, Environment and Health)
Representation of nature of science (NOS) within curricula including standards, grade level expectations, and textbooks and their alignment with each other to achieve teaching NOS is crucial. Thus, the aims of the study were to a) assess how NOS is portrayed in standards, grade level expectations and a teacher edition of seventh grade textbook of science and technology curriculum of Turkey and demonstrate b) how they aligned with each other to support teaching of NOS. A conceptual analysis was used to achieve the aims of the study by focusing on aspects of NOS , namely: the empirical, tentative, inferential, creative, theory-laden, and social dimensions of NOS; myth of “The Scientific Method”; nature of theories and laws; and social and cultural embeddedness of science. Analyses indicated that the targeted NOS aspects were insufficiently portrayed in these documents in that some important aspects of NOS (e.g., scientific theories and laws) are not included while some others (e.g., inferential and theory-driven) are implicitly represented. The findings also showed that the alignment between the curriculum and the textbook is not adequate to transfer the aims of the curriculum for NOS into classroom practices. Implications for curriculum developers and textbook publishers were also discussed.